A risky tale of two countries - Probohudono, A.; Tower, Gregory; Rusmin, Rusmin (Emerald Group Publishing Limited, 2013)
Purpose – The purpose of this paper is to provide a comparative analysis of the communication of the five major categories of risk (business, strategy, market and credit risk disclosure) over the volatile 2007-2009 global financial crisis (GFC) time period between Indonesia and Malaysia manufacturing listed companies. Design/methodology/approach – A total of 300 firm years data are collected consisting of a random sample of 100 manufacturing listed companies’ annual reports for fiscal year-ends from 2007 to 2009. The reports include 50 annual reports of manufacturing companies per country, listed in the stock exchanges of Indonesia and Malaysia for this three-year GFC time period. This research adopts a researcher-constructed risk disclosure index (RDI) to create an index measuring the extent of risk disclosure by listed firms. Findings – Key findings from statistical analysis are that country of incorporation and size help predict risk disclosure levels. Malaysian companies have significantly higher levels of business risk in 2007 and operating risk communication in 2007, 2008 and 2009 than Indonesian companies.These two countries have similar economic scenarios as developing countries which often have higher “business” risk for companies, but Malaysian companies disclose more risk information than Indonesia. The overall low disclosure levels (27.46-32.92 per cent for Indonesian companies and 35.20-39.04 per cent for Malaysian companies) highlight the potential for far higher communication of key risk factors in these two countries. Originality/value – This study is important as it contributes to the literature by providing comparative insights into the voluntary risk disclosure practices of manufacturing companies in the two important Asian countries (Indonesia and Malaysia) over the GFC time period. There is lack of risk disclosure studies in manufacturing companies, especially in these two sample countries.